Maximizing Tc by tuning nematicity and magnetism in FeSe1−xSx superconductors. Issue 1 (December 2017) - Matsuura, K.; Mizukami, Y.; Arai, Y.; Sugimura, Y.; Maejima, N.; Machida, A.; Watanuki, T.; Fukuda, T.; Yajima, T.; Hiroi, Z.; Yip, K.; Chan, Y.; et al.
Abstract A fundamental issue concerning iron-based superconductivity is the roles of electronic nematicity and magnetism in realising high transition temperature (T c ). To address this issue, FeSe is a key material, as it exhibits a unique pressure phase diagram involving non-magnetic nematic and pressure-induced antiferromagnetic ordered phases. However, as these two phases in FeSe have considerable overlap, how each order affects superconductivity remains perplexing. Here we construct the three-dimensional electronic phase diagram, temperature (T ) against pressure (P ) and isovalent S-substitution (x ), for FeSe1−x Sx . By simultaneously tuning chemical and physical pressures, against which the chalcogen height shows a contrasting variation, we achieve a complete separation of nematic and antiferromagnetic phases. In between, an extended non-magnetic tetragonal phase emerges, whereT c shows a striking enhancement. The completed phase diagram uncovers that high-T c superconductivity lies near both ends of the dome-shaped antiferromagnetic phase, whereasT c remains low near the nematic critical point. The overlap between different phases has hindered the understanding of how each phase affects superconductivity in FeSe. Here, Matsuura et al. achieve a complete separation of non-magnetic nematic and antiferromagnetic phases for FeSe1-x Sx, observing a tetragonal phase in between with a strikingly enhancedT c .